Application of FussionClassify for data classification - Duraj, Agnieszka (Wydawnictwo Politechniki Łódzkiej, 2013)
In the published articles and works there are solutions regarding data fusion. However, there is not any verification as for the efficiency of classifiers in the case of many sources of data given simultaneously. It is, seemingly, a very significant problem to be considered in the case of e.g. data fusion in intelligent traffic control. The intention of the author is to prepare the tools for classification of data which come from various sources. They can be sets (data files) prepared by the user of application, but they can also be one (or many) sets from the UCI machine learning repository (http://archive.ics.uci.edu/ml/).